YOUTH ENTREPRENEURIAL DEVELOPMENT THROUGH CREATIVE PRODUCT BRANDING WORKSHOPS - Friend Zakharia; Heriyanto Heriyanto; Ajeng Faizah Nijma Ilma (Adiba Aisha Amira, 2025)
Youth entrepreneurship development is a crucial strategy for fostering economic independence and creating new jobs amidst increasingly complex global challenges. This community service program, titled